Upaya Peningkatan Kemandirian Belajar Remaja Melalui Layanan Bimbingan Kelompok Kolaboratif - Triati Lestari Salau; Loban, Maria Natalia; Jumingke Debora Dangu (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this activity is to increase adolescents independence in personal, social, learning and career aspects. There are two methods of implementing activities. First, identify the intelligence abilities of adolescents. The second method, through the provision of collaborative group guidance services consisting of 4 stages, namely, 1) Formation Stage; 2) Transitional Stage; 3) Activity Stage; 4) Termination Stage. At the activity stage, various informative, educative and innovative service strategies are used. The analysis technique used descriptive qualitative analysis and categorical analysis. The result of this activity was founding the majority of adolescents with varied cognitive abilities (IQ); the occurrence of dynamic group dynamics in group guidance; and foster their commitment to increase learning independence. Thus, this activity can improve the ability of adolescents to develop and grow with their own learning capacity appropriately and confidently.